Pcdhβ deficiency affects hippocampal CA1 ensemble activity and contextual fear discrimination - Hirotaka Asai; Noriaki Ohkawa; Yoshito Saitoh; Khaled Ghandour; Emi Murayama; Hirofumi Nishizono; Mina Matsuo; Teruyoshi Hirayama; Ryosuke Kaneko; Shin-ichi Muramatsu; Takeshi Yagi; Kaoru Inokuchi (Molecular Brain, 2020)
Abstract Clustered protocadherins (Pcdhs), a large group of adhesion molecules, are important for axonal projections and dendritic spread, but little is known about how they influence neuronal activity. The Pcdhβ cluster is strongly expressed in the hippocampus, and in vivo Ca2+ imaging in Pcdhβ-deficient mice revealed altered activity of neuronal ensembles but not of individual cells in this region in freely moving animals. Specifically, Pcdhβ deficiency increased the number of large-size neuronal ensembles and the proportion of cells shared between ensembles. Furthermore, Pcdhβ-deficient mice exhibited reduced repetitive neuronal population activity during exploration of a novel context and were less able to discriminate contexts in a contextual fear conditioning paradigm. These results suggest that one function of Pcdhβs is to modulate neural ensemble activity in the hippocampus to promote context discrimination.